Literature and Nature: The Erasure of Dualism - Che Man, Siti Hajar; Muhammad, Suzana (ASPENSI, 2011)
ABSTRACT: The depiction of womenâs subjugation and subordination of women is prevalence and feminist critics determines to dismantle the ideology of patriarchal dominance to create awareness about the positioning and rules of women in society. This paper intends to explore the authorâs depiction of nature associated with the formation of womenâs self. Karen Warren (1997) indicates that trees, water, animal, toxics, and nature language are feminist issues because understanding them helps one understand the status and plight of women cross-culturally. The depiction of natural environment and the position of women will be explored in detail to understand and criticizes authorâs perception toward nature and woman. The authorâs uses of domestic animal like a bird and a cat to symbolize the womenâs need for companionship but this also connotes to women dependency. Womenâs uses of natural flower and faunas as womenâs fragrance are significance and the author acknowledges womenâs knowledge of natural products that are available around the house. The paper also explores the metaphors that are associated the portrayal of the unattended local trees that surrounding the neglected âRumah Limas potongan Perakâ house which relates the image of Sangeethaâs physical being. Using Taiping in Perak, Malaysia as the setting, the authorâs depiction of the natural floral and faunas is densely coalesced with the preservation of natural heritage that reflects the authorâs attitude toward nature and environment. Finally, this paper explores in detail the reciprocal relationship between literature and nature by examining natural heritages elements related to the northern region of peninsular Malaysia that uniquely illustrated through the novel. KEY WORD: Subordination, ecofeminist, companionship, patriarchal, and environment.Â Â About the Authors: Assoc. Prof. Dr. Siti Hajar Che Man is a Senior Lecturer at Literature Section, School of Humanities USM (Science University of Malaysia), 11800 Minden, Pulau Pinang, Malaysia; and Dr. Suzana Muhammad is also a Senior Lecturer at English Language and Literature Section, School of Humanities USM (Science University of Malaysia). They can be reached at: shajar@usm.my and szna@usm.myHow to cite this article? Che Man, Siti Hajar & Suzana Muhammad. (2011). âLiterature and Nature: The Erasure of Dualismâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.1(2) Desember, pp.157-170. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, ISSN 2088-1290.Chronicle of the article: Accepted (October 28, 2011); Revised (November 29, 2011); and Published (December 15, 2011).